Challenges for Agroforestry Research - Tejwani, K.G. (Indian Journal of Agroforestry, 2020)
The paper establishes the challenge and opportunity of agro forestry land use. Then, it lists eight challenges to agro forestry research and development namely challenge of (i) awareness & importance, (ii) need to identify nodal stakeholder, (iii) systematic approach, (iv) what to research, (v) mechanisms to decide what to research, (vi) research for whom, (vii) thinÂ  Spread of AF research, and (viiii) human resources management. It appears that though so far we have achieved fair results yet they could be much better and more effective. There is need of greater focus and effort on agro forestry research and development, since the Indian farms and lands outside forest carry more trees than the state forests.